2000
DOI: 10.12693/aphyspola.98.619
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectra of In0.30Se0.70Amorphous Films

Abstract: Amorphous films of In0.30 Se0.70 alloy thermally evaporated from one source onto borosilicate glass substrates were studied by Raman scattering at 300 K and 10 K. The Raman scattering spectra excited with 488 and 457.9 nm laser lines were recorded in a quasi-rectangular geometry with the use of a single channel spectrometer. All the Raman scattering spectra reveal a continuum spreading from the Rayleigh line up to about 250 cm -1 and rather featureless background due to second-order processes beyond it. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…Star symbols indicate Raman peaks related to vibrational modes of MoSe 2 phase [ 51 ] and square symbols indicate Raman peaks related to an amorphous In–Se phase. [ 44–47 ] The spectra are normalized to the noise of the baseline.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Star symbols indicate Raman peaks related to vibrational modes of MoSe 2 phase [ 51 ] and square symbols indicate Raman peaks related to an amorphous In–Se phase. [ 44–47 ] The spectra are normalized to the noise of the baseline.…”
Section: Resultsmentioning
confidence: 99%
“…The detected broad bands appear within the spectral regions that are characteristic of amorphous In-Se phases. [44][45][46][47] For the same chemical composition, Raman spectra of amorphous phases change notably with respect to the spectra of crystalline phases. [44,48] It has been reported that the amorphous In 2 Se 3 presents a broad band with a peak at 255 cm À1 and a broad band with a peak at 490 cm À1 , [44] while In x Se 1Àx presents a broad band with a peak that ranges from 190 to 255 cm À1 depending on the In/Se ratio.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations